Cerebral angiography normal anatomy and vascular pathology - Bradaéc, G. B. (Gianni Boris) 1939- (Springer, 2011)
Quot;Cerebral Angiography" is a comprehensive and well-illustrated guide to the diagnostic use of cerebral angiography. The first part of the book depicts in detail the normal appearance of the cerebral vessels on angiographic studies. Sound knowledge of this normal vascular anatomy and clinical function is vital for correct interpretation of the clinical significance of the pathological processes addressed in the second part of the book. The latter include vascular abnormalities, including angiomas, fistulas, and aneurysms; atherosclerotic and non-atherosclerotic stenosis and occlusion.